Epidemiological and Clinical Characteristics of Deceased Patients with COVID-19 in Chitwan and Pokhara: A Multicentric Study - Adhikari, BhojRaj; Mallik, Mukesh; Subedi, Nuwadatta; Wasti, Harihar; Ghimire, Babita; Paudel, Sabita (Journal of College of Medical Sciences-Nepal, 2024)
Background Appearance and reappearance of COVID-19 pandemic is a major global health problem seeking attention because of its high mortality and spreadability. In Nepal, as of the report of 24th April 2022 published by Ministry of Health and Population, there were 97873 detected cases of COVID-19 and 11951 deaths attributable to the pandemic. Reports suggest that there is variation in mortality rate across the clinical and demographic features of the population. Therefore, we aimed to find out the clinical features and demographic characteristics of the people who died in Chitwan and Pokhara due to COVID-19. Methods This is a quantitative descriptive cross-sectional study conducted from the data of record file of Bharatpur hospital and those of Gandaki Medical College which are representative of the patients who died due to COVID-19 in the respective hospitals. Descriptive statistical parameters like frequency, percentage, mean, interquartile range etc. were calculated. Results We found that mean age of the people dying of COVID-19 was 60.12 ±15.97 years. Number of males [163 (67.92%)] dying of COVID-19 was slightly more than twice the number of females [77 (32.08%)] dying due to the same. People with respiratory diseases and/or other comorbidities were greater among those who died due to the pandemic and died within eight number of average days after getting symptoms. Conclusions Old-aged people and males are at greater risk of death due to COVID-19. People with respiratory diseases and other comorbidities have higher chances of mortality.